Analysis of Gen Z's Readiness to Leverage AI in Green Jobs - Bening Kalimasada Aura Keindahan; Muhamad Azami Nasri (Pusbindiklatren Bappenas, 2025)
As an environmental issues enthusiast and tech-savvy generation, Gen Z is poised to benefit from green and digital transitions by utilizing AI in their preferred green jobs. This study uses a qualitative approach to describe Gen Z's readiness to use AI in green jobs based on the Readiness for Organizational Change theory. The study employed purposive sampling to interview 19 Gen Z employees in green jobs (academia, business, community, and public sectors), supported with literature reviews. The research examines readiness through four key aspects: appropriateness, management support, change efficacy, and personal valence. It also analyzes Gen Z’s perceptions of AI’s importance, benefits, uses, and the challenges in the application. The findings show that Gen Z employees view AI as essential for enhancing work efficiency and productivity, though they face some challenges. Various organizational approaches to AI adoption highlight that AI integration is not just technological, but also cultural. This research offers insights for organizations to create an enabling environment to use AI effectively. Furthermore, this study encourages the organization’s management to gain a deeper understanding of Gen Z employees’ application of AI in green jobs to support their workforce in adapting to technological advancements.